2019
DOI: 10.4236/nr.2019.1012028
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Soil Organic Matter and Soil Organic Carbon Stocks in Semi-Arid Area of Northeastern Syria

Abstract: Although soil organic matter (SOM) forms a small portion of the soil body. Nevertheless, it is the most important component of the soil ecosystem, as well as of the carbon global cycle. In the semi-arid environment, there has been little research on the spatial distribution of SOM and soil organic carbon (SOC) stock. In this study, stratified random samples of total 30 soils were collected from two different soil depth (topsoil, subsoil) of Al Balikh plain and used for mapping the spatial variability of SOC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This indicates the need for developing and utilizing the land, especially previously overlooked areas. In this respect, the large soil resources of arid regions provide a potential agricultural habitat and comprise around 16% of the planet's land surface [3]. Most developing nations with rapid population expansion are located in arid and semi-arid regions.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the need for developing and utilizing the land, especially previously overlooked areas. In this respect, the large soil resources of arid regions provide a potential agricultural habitat and comprise around 16% of the planet's land surface [3]. Most developing nations with rapid population expansion are located in arid and semi-arid regions.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the range suggests that SOC stock shows strong spatial autocorrelation than TN stock in all the exclosures and adjacent open grazing. The slightly higher nugget of TN than SOC stock implies a random and inherent variability of TN stock (Husein et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At the sampling points, soil samples were collected from a depth of 30 cm for SOC content, pH, and soil texture determination. Studies have shown that SOC is higher in the topsoil and decreases exponentially with depth [32][33][34]. In addition, the 30 cm soil depth is considered the most relevant soil depth for SOC estimation because it is the most biologically active layer of the soil [35] and is most affected by land management practices, particularly in the agricultural system (ploughing) [36].…”
Section: Sampling Designmentioning
confidence: 99%